2020
DOI: 10.1111/jdi.13274
|View full text |Cite
|
Sign up to set email alerts
|

Low birthweight is associated with type 2 diabetes mellitus in Japanese adults: The Toon Health Study

Abstract: Aims/Introduction Low birthweight is reportedly associated with type 2 diabetes mellitus; however, this association has not been confirmed in the Japanese population, and whether high birthweight is associated with type 2 diabetes mellitus is controversial. We aimed to investigate the association between birthweight and type 2 diabetes mellitus among a general Japanese population. Materials and Methods Overall 1,135 middle‐ to old‐aged Japanese men and women were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 37 publications
3
11
0
12
Order By: Relevance
“…The simplified results of the whole study also suggest that exposure to famine in early life might be a protective factor for obesity and a risk factor for metabolically unhealthy status. A study based on the Beijing Child and Adolescent Metabolic Syndrome Study (BCAMS) found that low birth weight was an independent risk factor for MUNO phenotype, which is consistent with the results of our study, because birth weight is a reflection of the intrauterine nutritional environment and a good measure of nutritional status in early life ( 45 47 ). A few studies have suggested that an adverse intrauterine environment could permanently affect the function of metabolism-related tissues through epigenetic modifications, thus increasing the risk of metabolic abnormalities in adulthood ( 48 , 49 ).…”
Section: Discussionsupporting
confidence: 92%
“…The simplified results of the whole study also suggest that exposure to famine in early life might be a protective factor for obesity and a risk factor for metabolically unhealthy status. A study based on the Beijing Child and Adolescent Metabolic Syndrome Study (BCAMS) found that low birth weight was an independent risk factor for MUNO phenotype, which is consistent with the results of our study, because birth weight is a reflection of the intrauterine nutritional environment and a good measure of nutritional status in early life ( 45 47 ). A few studies have suggested that an adverse intrauterine environment could permanently affect the function of metabolism-related tissues through epigenetic modifications, thus increasing the risk of metabolic abnormalities in adulthood ( 48 , 49 ).…”
Section: Discussionsupporting
confidence: 92%
“…Their findings also suggested a high prevalence of diabetes in the "small" birth weight group for women (17.8%), which was higher than those in the "medium" (2.9%) and the birth weight recorded in the maternal and child health handbooks and other related content provided by some participants; and the sub-group analysis with objective birth weight almost showed similar results. Previous studies conducted in Japan have indicated associations between birth weight and adverse conditions such as diabetes and hypertension [34][35][36][37][38][39][40] . However, few epidemiologic studies have targeted middle-aged populations because most reports have focused on individuals during their childhood or young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The association between LBW and future health problems among preterm infants was analyzed in several previous articles, but these studies did not address the causes for preterm birth [ 1 , 18 ], and other reports regarding the causes for LBW did not even mention the gestational weeks at birth [ 2 , 3 , 5 ]. Since the effects on lifelong healthcare of children might vary depending on the causes for LBW, we were also concerned that these analyses may have included cases that should have been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with LBW at delivery are known to have a higher risk of not only infant morbidity and mortality but also poor educational achievement, disability, and the development of metabolic diseases (i.e., type 2 diabetes, cardiovascular disease, and hypertension) in the future [1][2][3][4]. A recent report has indicated that LBW is associated with an increased risk of type 2 diabetes in Japanese adults [5]. Therefore, Normile D (2018) raised concerns regarding the future of Japanese healthcare in relation to the increasing number of neonates with LBW [6].…”
Section: Introductionmentioning
confidence: 99%